Association Of Micro RNA And Postoperative Cognitive Dysfunction: A Review - Yazit N.A.A.; Juliana N.; Das S.; Teng N.I.M.F.; Fahmy N.M.; Azmani S.; Kadiman S. (Bentham Science Publishers, 2024)
Indexed by WOS/Scopus/ERA